Mechanisms of Cellular Activation by Platelet Microparticles - Barry, Orla P.; FitzGerald, Garret A. (Thrombosis and Haemostasis, 1999)
Eukaryotic cells, after activation, shed components of their plasma membranes into the extracellular space.1,2 Such fragments may include cytoplasmic elements and are known colloquially as microparticles (MPs). Monocytes,3 lymphocytes,4 endothelial cells,5 erythrocytes,6 and granulocytes7 have been shown to vesiculate either in vitro or in vivo. MPs from other sources have also been reported to exist in vivo.8,9 In addition, platelets have been found to vesiculate following activation by agonists.10,11 Platelets activated with collagen and/or thrombin, by the Ca2+ ionophore A23187 or the complement protein C5b-9, induce platelet microparticle (PMP) formation. While the effect of these agonists is to increase platelet cytosolic Ca2+ concentration, it has been suggested that calpain activation,12-14 cytoskeletal reorganization,12,14,15 protein phosphorylation14 and phospholipid translocation16,17 also may have roles in PMP formation.Shear stress has been shown to induce platelet vesiculation. The mechanisms involved include the binding of von Willebrand factor (vWF) to either glycoprotein (GP)-Ib or GP IIb/IIIa.18 These in vitro observations are supported by an ex vivo model of high arterial shear stress. High shear stress, as pertains in the atherosclerotic vasculature, was shown to activate platelets and trigger PMP formation. Meanwhile, under physiological or simulated shear stress conditions in arteries with a minor degree of stenosis, no vesiculation occurred.19Platelet microparticles contain surface receptors for both factor VIII, a cofactor in the tenase enzyme complex,20 and factor Va (which assembles with factor Xa to form the prothrombinase complex).10 While a transient expression of platelet membrane factor VIII binding has been reported, more stable factor VIII and factor Va has been reported for PMPs.20 High- and low-affinity binding sites for activated factor IX are also present on PMPs.21 Thus, PMPs have the potential to provide procoagulant activity at a distance from the site of platelet activation and for a longer period than activated platelets. Also, PMPs possess anticoagulant properties.22 These PMPs can bind protein S, an anticoagulant plasma protein responsible for degradation of the phospholipid-bound coagulation factor Va and factor VIII and which supports the binding of both protein C and activated protein C (APC). Coupled to the same platelet stimulation reactions, PMPs possess both pro- and anticoagulant properties. The relative distribution of pro- and anticoagulant activity between platelets and PMP remains approximately the same, irrespective of the agonist used, with approximately 25% of both activities associated with PMP. Furthermore, a recent study reported that protein C inhibitor, a member of the serpin family secreted from activated platelets, binds preferentially to the phosphatidylethanolamine (PE) of platelet membranes and PMPs, and efficiently inhibits phospholipid-bound APC.23Similar to PMPs, MPs released from monocytes, lymphocytes, erythrocytes, and granulocytes demonstrate procoagulant activity, but whether they display anti-coagulant activity remains to be shown. The density of aminophospholipids also has been shown to be greater on PMPs than on remnant platelets.24,25 This may account for the preferential binding to PMPs over platelets of factor VIII,20 factor Va,10 and factor IXa.21 The PMP surface may provide the optimal phosphatidylserine (PS) level required by the binding sites of these blood clotting factors. Preferential binding of these critical factors favor the participation of PMPs in hemostatic protection and may explain the lack of bleeding symptoms in patients with autoimmune thrombocytopenia associated with high levels of PMPs.26Elevated levels of PMPs in vivo have been reported for patients with activated coagulation and fibrinolysis,27 unstable angina,28 diabetes mellitus,29 sickle cell anemia,30 and human immunodeficiency virus (HIV).31 Recently, it was demonstrated for the first time that PMPs generated in vivo can stimulate coagulation.32 Procoagulant PMPs generated during coronary bypass surgery, especially in pericardial blood, supported coagulation via a tissue factor (TF)/ factor VII-dependent and factor XII-independent pathway.The functional importance of PMPs in human disease has not been well-defined. This is despite their pro- and anticoagulative properties10,16,20,22 and the convincing evidence that the PMP surface possesses the platelet—endothelium attachment receptors, glycoprotein GP IIb/IIIa, Ib, and IaIIa33-35 and P-selectin.34 Despite the association of PMPs with a range of clinical abnormalities,26-31,36 it remains unsolved whether persistent platelet activation, with concomitant formation of PMPs, is merely a consequence of the disease or reflects the influence of previously formed PMPs in the circulation.PMPs have become a popular focus of research, for both clinical and basic investigation. Recently, the possibility that MPs might, themselves, evoke cellular responses in the immediate microenvironment of their formation has been suggested. For example, endothelial cell activation by thrombin results in vesicle shedding, which, in turn, activates neutrophils and enhances their propensity to adhere to endothelial cells.37 Similarly, MPs shed from platelets activated with Staphylococcus aureus α-toxin induce platelet aggregation.38The role of PMPs in modulating their local environment is the subject of this review. An overview of the mechanism(s) of cellular activation by PMPs will be provided. PMP-induced activation of platelets, human umbilical vein endothelial cells (HUVECs), monocytes, and U-937 (human promonocytic leukemia) cells have been used as models for assessing the possible biological effects of PMPs in vivo.